ARTISTIC IMAGE AS A REFLECTION THE PROCESS OF SOCIALIZATION OF PERSONALITY (Pedagogy of Higher and Secondary Education, 2006)
The article deals with the problem of en image as a semiotic unit of visual communication and its functional ability during persons socialization through the common function of culture.